Theoretical bases of multidimensional modeling of sustainable development in investment and construction activities - Sborshchikov Sergey Borisovich (Vestnik MGSU, 2014)
In the article the system processes of investment and construction activities (ISA) are considered as a set of economic space and time. The concept of economic space contains a generalized representation of the properties of technical and economic system in the initial state of its development. The space of investment and construction activities is a techno-economic system, the space, in which the movement is possible within the framework of sustainable development. A characteristic feature of economic space is its unity and indivisibility. The concept of economic space is closely related to the concept of economic time. The transition from one state of techno-economic system to another is described by the input and output variables. The task of ISA is to achieve optimal conditions for the rational use of system resources. The article identifies and discusses ISA subsystems and their interaction in the coordinate system. The space investment and construction activities encompasses a set of core and auxiliary processes, the behavior of techno-economic system, its mode of functioning in the context of sustainable development.